Pengaruh ROA , ROE, Dan DER Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di BEI - Nurhayati; Deny Yudiantoro (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to examine the effect of ROA, ROE, and DER on stock prices in banking companies listed on the IDX for the 2017-2020 period. The population in this study is banking companies listed on the IDX. The samples in this study were 11 banking companies. This study uses a panel regression analysis method, which is processed using the e- views 10 programs. The coefficient of determination R2 shows that the ROA, ROE, and DER variables are able to influence stock prices by 21.3%. While the remaining 78.7% are leftover from other variables that are not used in. Partially ROA and ROE have a positive and significant effect on stock prices, DER has a negative and insignificant effect on prices. Simultaneously, the variables ROA, ROE, and DER affect stock prices.